Die mittelalterlichen Handschriften in der Bibliothek des Augustiner Chorherrenstiftes Neustift - Schretter-Picker, Claudia (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
he Augustinian Monastery of Neustift, founded in 1142, houses 92 medieval manuscripts in its collection today; these have now become accessible through the work of an interdisciplinary team of experts, in accordance with the guidelines of the Austrian Academy of Sciences. The catalogue, which takes all codicological aspects into account, is supplemented by an extensive introduction, indices and appendices. Around 50 Neustift manuscripts have been kept at the University and State Library of Tyrol in Innsbruck since 1809. Therefore, the publication sees itself as an essential contribution to the virtual reconstruction of the former Neustift library and as important basic werk for further research.